Taghayyur as a Theoretical Basis of Muslim and Non-Muslim Relations at the Nahdlatul Ulama's Bahthul Masa'il - Mohammad Rofiqul A’la; Rosihon Anwar; Nurwadjah Ahmad; Dody S. Truna (AL-TAHRIR, 2021)
Abstract: This study discusses the history of fatwas on Muslim-Non-Muslim relations issued by the Bahthul Masa'il Institute (LBM) of Nahdlatul Ulama from 1926 to 2019. This research is a type of qualitative research focused on studying LBM written materials. The perspective used is the Study of Religion with a theoretical analysis from Joachim Wach regarding the forms of expression of religious experience, especially in the sociological form. This study finds that, historically, NU issued fatwas by considering such sociological aspects that taghayyur (law change) method is used in law enforcement. By adhering to this principle, NU has formulated fatwas to maintain Muslim-non-Muslim relations under the umbrella of the Unitary State of the Republic of Indonesia. In this regard, NU argues that non-Muslims in Indonesia cannot be categorized in terms of the infidel in the nation-state because non-Muslim citizens in the nation-state context are not second-class citizens as contained in the concept of infidel with various types. The implication is the increasing quality of inter-religious relations that are increasingly harmonious in a plural society.الملخص :تناقش هذه الدراسة تاريخ الفتاوى حول العلاقات بين المسلمين وغير المسلمين الصادرة عن معهد بهتول المسائل (LBM)  لتابع لنهضة العلماء من عام  1926 إلى عام  2019. هذا البحث هو نوع من البحث النوعي الذي يركز على دراسة المواد المكتوبة من قبل  LBM. المنظور المستخدم هو دراسة الدين مع تحليل نظري من Joachim Wachفيما يتعلق بأشكال التعبير عن التجربة الدينية ، وخاصة في الشكل الاجتماعي. توصلت هذه الدراسة إلى أنه تاريخياً ، أصدرت جامعة النيل فتاوى من خلال النظر في الجوانب الاجتماعية ، وبالتالي استخدام طريقة التغايور )تغيير القانون  (في إنفاذ القانون. بالالتزام بهذا المبدأ ، قامت NU بصياغة فتاوى للحفاظ على العلاقات بين المسلمين وغير المسلمين تحت مظلة الدولة الموحدة لجمهورية إندونيسيا. في هذا الصدد ، يجادل NU بأنه لا يمكن تصنيف غير المسلمين في إندونيسيا من حيث الكفار في الدولة القومية لأن المواطنين غير المسلمين في سياق الدولة القومية ليسوا مواطنين من الدرجة الثانية كما هو وارد في مفهوم الكفر. بأنواع مختلفة. المعنى الضمني هو الجودة المتزايدة للعلاقات بين الأديان التي تزداد انسجامًا في مجتمع تعددي.Abstrak: Penelitian ini membahas riwayat fatwa hubungan Muslim-Non-Muslim yang dikeluarkan oleh Lembaga Bahthul Masa'il (LBM) Nahdlatul Ulama dari tahun 1926 hingga 2019. Penelitian ini merupakan jenis penelitian kualitatif yang difokuskan untuk mengkaji bahan tertulis LBM. Perspektif yang digunakan adalah kajian agama dengan analisis teori dari Joachim Wach mengenai bentuk-bentuk ekspresi pengalaman beragama, terutama dalam bentuk sosiologis. Studi ini menemukan bahwa dalam sejarahnya, NU mengeluarkan fatwa dengan mempertimbangkan aspek sosiologis, sehingga memakai metode taghayyur (perubahan hukum) dalam penegakan hukum. Dengan berpegang pada prinsip ini, NU telah merumuskan fatwa-fatwa untuk menjaga hubungan Muslim-non-Muslim di bawah payung Negara Kesatuan Republik Indonesia. Dalam kaitan ini, NU berpendapat bahwa non-Muslim di Indonesia tidak dapat dikategorikan dalam istilah kafir dalam negara-bangsa karena warga negara non-Muslim dalam konteks negara-bangsa bukanlah warga kelas dua sebagaimana termuat dalam konsep kafir dengan berbagai jenisnya. Implikasinya adalah meningkatnya kualitas hubungan antar umat beragama yang semakin harmonis di masyarakat plural.